2017
DOI: 10.1155/2017/5202684
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Risk of Hepatocellular Carcinoma

Abstract: The occurrence of hepatocellular carcinoma (HCC) is two to three times higher in patients with diabetes mellitus (DM), the prevalence of which is increasing sharply worldwide. The purpose of this review was to describe clinical links between DM and HCC and potential biological mechanisms that may account for this association. We evaluated the role of potential pathways that could account for the development of HCC with different etiologies in the presence of DM. In addition, we also briefly discuss the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 162 publications
(166 reference statements)
3
50
0
2
Order By: Relevance
“…Other studies confirmed these findings, attributing from 2 to 3 times increased risk and a considerable proportion of these studies only included patients with negative serology for viral hepatitis. 7 The complex process of carcinogenesis involves several stages, that can be summarized as follows: endogenous hyperinsulinemia (insulin resistance), exogenous hyperinsulinemia (treatment with insulin or secretagogues), hyperglycemia, increased proinflammatory state and oxidative stress make damage to the genetic code more likely, increased angiogenesis and cell proliferation and reduced apoptosis rate. 8 Therefore, since diabetes is a risk factor for hepatic neoplasms and our patient had negative serology for viral hepatitis, the fact that she had had diabetes for a long time supports the likelihood of a relationship between the two diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies confirmed these findings, attributing from 2 to 3 times increased risk and a considerable proportion of these studies only included patients with negative serology for viral hepatitis. 7 The complex process of carcinogenesis involves several stages, that can be summarized as follows: endogenous hyperinsulinemia (insulin resistance), exogenous hyperinsulinemia (treatment with insulin or secretagogues), hyperglycemia, increased proinflammatory state and oxidative stress make damage to the genetic code more likely, increased angiogenesis and cell proliferation and reduced apoptosis rate. 8 Therefore, since diabetes is a risk factor for hepatic neoplasms and our patient had negative serology for viral hepatitis, the fact that she had had diabetes for a long time supports the likelihood of a relationship between the two diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients are identified when the disease is progressive. As a result, recognition and chemopreventive treatments of persons at risk for HCC indicate one of the most excellent approaches for decreasing death due to this cancer (7). Various risks cause liver cancer contain hepatitis C virus (HCV) infection, hepatitis B virus infection, and over intake of alcohol and non-alcoholic fatty liver, which, nevertheless, cannot describe the rapid rise of liver cancer in certain areas (7).…”
Section: Effects Of Metformin On Liver Cancermentioning
confidence: 99%
“…On the other hand, epidemiologic data shows a rising part for diabetes in the growth of HCC. Respective risk of HCC is two to three times more in patients with type II diabetes (7). Meanwhile, metformin controls basal glucose production by controlling glycogenolysis and gluconeogenesis in the liver and rising glucose uptake in the muscle (8).…”
Section: Effects Of Metformin On Liver Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Sucrose consumption causes fat accumulation in the liver, and subsequent development of hepatic insulin resistance, an independent risk factor for NAFLD (DiNicolantonio et al, 2015). The hyperinsulinemia due to insulin resistance increases precursors for hepatic fibrosis, reduces β-oxidation of fatty acids, and increases the generation of free radicals (Li et al, 2017;Paradis et al, 2001;Sun et al, 2018). The harmful effects of sugar-enriched diets and the association between sugar and NAFLD were comprehensively reviewed by Wong et al (2016) and Jensen et al (2018), respectively.…”
Section: Introductionmentioning
confidence: 99%